2001
DOI: 10.1002/mar.1038
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and ability as predictors of play behavior in state‐sponsored lotteries: An empirical assessment of psychological control

Abstract: This research explores the interaction of motivation and ability to explain individuals' level of participation in state-sponsored lotteries. The motivation -ability framework is considered from the perspective of perceived control wherein Rotter's (1966) locus of control serves as a perceived ability to influence lottery outcomes, and the Burger and Cooper (1979) desire for control serves as a motivation to play. With the use of a sample of adult consumers residing in a state with a government-sponsored lotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
3
17
0
1
Order By: Relevance
“…Their investigation concluded that nonpurchase motivations were more helpful in explaining the level of lottery play than purchase motivations. Another study by Sprott, Brumbaugh, and Miyazaki (2001) found that heavy buyers of lotteries (split at the median) have a higher internal locus of control, and a greater desire to control compared to light buyers. Miyazaki, Brumbaugh, and Sprott (2001) suggest that consumers' misconceptions on their ability to control random events are likely to affect their attitudes and behaviors toward the purchase of lottery.…”
Section: Recent Research In Gamblingmentioning
confidence: 96%
“…Their investigation concluded that nonpurchase motivations were more helpful in explaining the level of lottery play than purchase motivations. Another study by Sprott, Brumbaugh, and Miyazaki (2001) found that heavy buyers of lotteries (split at the median) have a higher internal locus of control, and a greater desire to control compared to light buyers. Miyazaki, Brumbaugh, and Sprott (2001) suggest that consumers' misconceptions on their ability to control random events are likely to affect their attitudes and behaviors toward the purchase of lottery.…”
Section: Recent Research In Gamblingmentioning
confidence: 96%
“…However, research has shown that only a very small portion (i.e., 2%) of adult gamblers can be categorized as pathological gamblers (Shaffer et al 1999). As a result, recent research has been generally treating gambling activity as a common pastime (Lam 2007, Mizerski et al 2004, Nisbet 2009, Oh and Hsu 2001, Sprott et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Since perceived control has been found to influence behavior (Skinner, 1996;Sprott, Brumbaugh, & Miyazaki, 2001), it is important to understand how health locus of control would influence consumer behavior related to procuring medications online (i.e., channel choice). Health locus of control has been widely acknowledged as an antecedent to health-related behavior by researchers Seeman & Seeman, 1983).…”
Section: Health Locus Of Controlmentioning
confidence: 99%